Design and Evaluation of Metoprolol Tartrate Containing Buccal Tablets (Dhaka University Journal of Pharmaceutical Sciences, 2012)
Metoprolol tartrate is a selective ?-1 adrenergic antagonist used in the treatment of the cardiovascular system, especially hypertension. It is readily and completely absorbed from the gastrointestinal tract but is subjected to considerable first- pass metabolism having half-life of 3 to 4 hr. It has 12% oral bioavailability. These physicochemical properties of metoprolol tartrate (undergoing considerable first- pass metabolism, low molecular weight) make it suitable candidate for administration by buccal route. Bilayered buccal tablets of metoprolol tartrate were prepared by direct compression method using combinations of polymers (carbopol 934p along with sodium carboxy methyl cellulose, sodium alginate and hydroxy propyl methyl cellulose K4M), using mannitol as a channeling agent and ethyl cellulose as a backing layer. The tablets were evaluated for physical and biological parameters. Among the 15 formulations, the formulation FA1 containing sodium alginate (34.00% w/w of matrix layer), Carbopol 934p (6.0% w/w of matrix layer) and mannitol (channeling agent, 8.0% w/w of matrix layer) was found to be promising, which showed t25%, t50%, t70% values of 0.42, 2.45, 4.48 hr respectively and in vitro drug release    of 86.04% in 8 hr along with satisfactory bioadhesive strength (5.00±0.10 g). Stability studies on the promising formulations indicated that there are no significant changes in drug content and in vitro dissolution characteristics (p